Gamification of Indonesia Geospatial Data as An Advanced and Sustainable Digital Geotourism Media - Adnan Hasyim Wibowo; Ralfy Ruben Rialdi (International Journal of Geotourism Science and Development, 2023)
Easier internet access makes space and time boundaries in the real world no longer significant challenges in the virtual world. This means that tourists do not always have to physically visit the places they want. Digital tourism has become a new realm that is positively growing in the current era. Unfortunately, even though this is in great demand in various parts of the world, Indonesia is still not fully exploiting (in positive terms) this potential. Geospatial data and technology can be the primary key in solving these problems and opening broader development potential although data utilization and optimization of existing geospatial technology still need improvement. The various existing innovations are still relatively conventional and do not attract youngsters’ attention. An advanced but fun project is, therefore, needed to bridge geospatial experts, creative innovators, and the youth to develop and accelerate digital tourism in Indonesia. Gamification is a promising solution to this problem. This research uses the 4D method (define, design, develop, disseminate). The gamification resulting from the 4D method is used by researchers as an instrument to compare with conventional tourism media to determine public interest and promotional reach for traveling to Indonesia. The primary data used in this project is the Indonesia Shuttle Radar Topography Mission (SRTM) data. The first part of the results discusses the gamification model that the researchers propose. This model uses Minecraft as a basis for gamification in implementing the exploitable open-world concept. The second part of the results discusses the validation and potential of the gamification that the researchers created through the triangulation of survey data, interviews, and literature.